Association Abnormal Levels of Serum Interleukin-33, Interleukin-23 with Oxidant-Antioxidants Status in patients with Acute Liver Failure - zaid, Auhood k.; Sayer, Sarah A (University of Thi-Qar Journal of Science, 2022)
Acute liver failure (ALF) is not itself a disease, but a condition that develops rapidly in response to some forms of liver injury. There is no evidence to prove an association between serum IL-33 with oxidant- antioxidant status in patients of liver failure. The present study aimed to evaluate the possible association between these parameters and to investigation the prognostic role of interleukin-33 in liver failure disease by using the ROC curve. This study includes (30 patients and 30 controls ((were 17 men and 13 female)). During the period of 2021- 2022, patients and controls aged 30- 55 years. The results showed that there is a significant increase in the serum levels of ( MDA, NO, CP , IL-33 and IL-23) in patients group in comparison with controls group Furthermore, it was found that there is a positive correlation between IL-33 and ( IL-23, MDA, NO and Cp ).The ROC curve demonstrated that the levels of (IL-33, IL-23, MDA, NO and CP) have exhibited an good method for discriminating’ between healthy individuals and patients with acute liver failure .In Conclusion, our findings indicated that there is an association between abnormal serum IL-33 levels and Oxidant-Antioxidants Status. Moreover, the level of IL-33 can consider an early prediction biomarker for gestational diabetes. The use of ROC curve analysis confirmed thatIL-33 is effective for the diagnosis of liver failure.